Spectral induced polarization monitoring of induced calcite precipitation in subsurface sediments. Issue 1 (17th August 2022) - Placencia-Gόmez, Edmundo; Robinson, Judith; Slater, Lee; Qafoku, Nikolla P
SUMMARY: Co-precipitation of contaminants within the crystalline structure of calcite is a promising natural attenuation or remedial technology being considered at contaminated sites. We explore the sensitivity of the spectral induced polarization (SIP) method to induced calcite precipitation in natural sediments as a path forward to non-invasively monitor these sites. We performed time-lapse column experiments using phased (I–IV) injections over 40 d on natural sediments from the Hanford Site (WA, USA). In the phased injections, abiotic calcite precipitation was induced and confirmed to have occurred. Previous work on glass beads and homogeneous sand was limited to high frequency detection of calcite, however in this work we observed the development of two polarization mechanisms, one at high frequency (>100 Hz) and one at low frequency (<100 Hz). Based on the characteristic frequencies from the SIP high and low frequency regimes, characteristic length scales ( L ) were computed where the adsorption mode of Na + versus Ca 2+ was compared by using diffusion coefficients corresponding to Na + versus an arithmetically averaged value for Na + and Ca 2+ . Using the diffusion coefficient of Na +, the high frequency L was found to correlate well with the size of the calcite crystals. The low frequency L correlated well with the individual natural sediment grain sizes within the columns. During late experimental times (day 36 and 40), the characteristic low frequency in two of the experimental columns shifted to lower frequencies (<0.001 Hz) which may signify SIP sensitivity of the formed calcite with the sediment grains. In field applications, the development of a low frequency polarization length scale to monitor calcite precipitation is promising for field monitoring applications, however further laboratory work needs to be performed to examine the SIP sensitivity of calcite formation in the presence of natural sediments.